Tender coconut water attenuates heat stress-induced testicular damage through modulation of the NF-κB and Nrf2 pathways. Issue 10 (8th October 2018) - Kumar, Soumya Sundar; Manna, Krishnendu; Das, Asima
Abstract : Tender Coconut Water (TCW) prevents heat stress (HS)-induced testicular damage. Abstract : Tender coconut water (TCW), a well-known plant beverage, has been used as a stress-relieving traditional medicine since ancient times. It is also used to treat various ailments of disease, including hepatic disorders, renal disorders, gastric disorders and reproductive disorders. However, the reasons for its effectiveness as a natural antioxidant as well as its testicular protective effects against whole body heat stress (HS)-induced oxidative imbalance remain to be revealed. The present study aimed to elucidate the protective efficacy of TCW on HS-induced testicular damage in a murine system and to explore the possible mechanism of action. Standardized liquid chromatography-mass spectrometry (LC-MS) was used to detect the presence of active components in TCW. Male Wistar rats were exposed to acute HS with or without TCW treatment to evaluate the degree of testicular damage, which was monitored through histological as well as biochemical analysis. Assessment of endogenous antioxidant response and the modulation of signaling pathways associated with inflammation were also subjected to immunofluorescence and flow cytometric evaluation. Acute hyperthermia caused an elevation of excess generation of oxygen radicals following the suppression of antioxidant capacity and augmentation of lipid peroxidation in murine testicles, which was restored by treatment with TCW. The results also demonstrated marked phosphorylation of IKKα/β and IκBα following the activation of NF-κB-guided pro-inflammation upon HS. TCW treatment reversed the HS-induced proinflammatory state through activation of the Nrf2-assisted antioxidant response, which restored the testicular damage. TCW provided competent scientific evidence to substantiate the claims for its use in the treatment of HS-induced inflammation and inflammation-mediated testicular damage.